Evolution of reproductive strategies in coleoid mollusks. Issue 1 (February 2020) - Fuchs, Dirk; Laptikhovsky, Vladimir; Nikolaeva, Svetlana; Ippolitov, Alexei; Rogov, Mikhail
Abstract: Coleoid cephalopods exhibited two distinct reproductive strategies, resulting in small pelagic and large demersal hatchlings, both in the geologic past and recently. In ectocochleate cephalopods, the hatching event is recorded in shell structures (e.g., nepionic constrictions, ultrastructural shifts, or ornamentation differences). In contrast, well-defined hatching markers do not exist on coleoid shells. Changes in septal spacing may be evidence of hatching (e.g., some extant sepiids), but not in all fossil groups. In the present study, we subdivide the early ontogenetic shells of phragmocone-bearing coleoids (belemnoids, spirulids, and sepiids) into key architectural stages and describe their reference to the hatching event. Belemnoids exhibit three key stages, the second of which is here considered to occur shortly before or after hatching. In spirulids and sepiids, there is only one key stage. In Mesozoic belemnoids, spirulids, and sepiids, hatching accordingly occurred with a total shell length of less than 2 mm, which corresponds to mantle lengths of small planktonic hatchlings. Production of small pelagic hatchlings and thus small eggs was therefore the dominant reproductive strategy within the Coleoidea. The first evidence of enlarged hatchlings appeared during the Maastrichtian in Groenlandibelus. During the Eocene, the large-egg strategy apparently became more widespread, particularly in belosaepiids.